Enhanced antitumor immunity of VNP20009-CCL2-CXCL9 via the cGAS/STING axis in osteosarcoma lung metastasis - Yuming Wang; Qi Liu; Chong Zhao; Zhusheng Zhang; Weibin Zhang; Paul Castillo; Tianyi Liu; Elizabeth Ogando-Rivas; Haipeng Tao; Ruixuan Liu (Journal for ImmunoTherapy of Cancer)
Background Osteosarcoma (OS) with pulmonary metastasis remains challenging due to limited treatment options and the immunosuppressive nature of the tumor microenvironment (TME). Bacteria-mediated cancer therapy has emerged as a promising strategy for solid tumors but often suffers from limited efficacy due to the immunosuppressive TME, which restricts the intensity and durability of the antitumor immune response. To overcome these challenges, we engineered a novel Salmonella strain, VNP20009-CCL2-CXCL9 (VNP-C-C), leveraging the intrinsic tumor tropism of Salmonella typhimurium VNP20009 (VNP) and improving immune modulation through the recruitment of effector immune cells into the TME by the chemokines CCL2 and CXCL9.Methods VNP-C-C was genetically engineered through electroporation of Plac-CCL2-CXCL9 plasmid and validated in vitro. Its antitumor efficacy, immune regulation capacity and immunomodulatory mechanisms were evaluated in vitro by using OS cell lines and immune cells (dendritic cells (DCs) and macrophages (Mφs)) and in vivo by using both immunocompromised and immunocompetent mouse models of OS lung metastasis.Results VNP-C-C effectively accumulated within tumors, triggering immunogenic cell death and subsequently activating the cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) pathway, thereby robustly promoting type I interferon secretion. The chemokines CCL2 and CXCL9 amplified the immune response by recruiting DCs, Mφs, and T cells to the TME. This orchestrated immune modulation reprogrammed tumor-associated macrophages to an antitumor phenotype, induced DCs maturation, significantly increased T-cell infiltration and activation within tumors, and promoted systemic T-cell memory formation in peripheral lymphoid organs. These effects collectively inhibited OS lung metastasis progression and provided survival benefits in mouse models.Conclusion The engineered bacterial strain VNP-C-C effectively converts the OS lung metastatic TME into a pro-inflammatory milieu, thereby stimulating robust innate and adaptive immune responses. This offers a highly promising therapeutic avenue for OS lung metastasis with considerable translational potential in cancer immunotherapy.